ON THE METHODOLOGY OF SCIENTIFIC ACTIVITY IN DENTISTRY - Zaitsev, A.; Vatsenko, A.; Nikolishi, A.; Vyzhenko, E. (World of Medicine and Biology, 2014)
The article deals with the question of the correctness of the construction of diagrams Euler-Venn relatively cariogenic factors. The analyzed the compatibility and the subordination of chart elements. It is concluded that the need to make adjustments in the construction of these diagrams.